Replica exchange molecular dynamics simulation of the coordination of Pt(ii)-Phenanthroline to amyloid-β. Issue 60 (30th October 2019) - Turner, Matthew; Mutter, Shaun T.; Kennedy-Britten, Oliver D.; Platts, James A.
Abstract : Replica exchange molecular dynamics are used to explore the conformational freedom of amyloid-βbound to Pt(phenanthroline), highlighting important differences in secondary and tertiary structure from the metal-free peptide. Abstract : We report replica exchange molecular dynamics (REMD) simulations of the complex formed between amyloid-β peptides and platinum bound to a phenanthroline ligand, Pt(phen). After construction of an AMBER-style forcefield for the Pt complex, REMD simulation employing temperatures between 270 and 615 K was used to provide thorough sampling of the conformational freedom available to the peptide. We find that the full length peptide Aβ42, in particular, frequently adopts a compact conformation with a large proportion of α- and 3, 10-helix content, with smaller amounts of β-strand in the C-terminal region of the peptide. Helical structures are more prevalent than in the metal-free peptide, while turn and strand conformations are markedly less common. Non-covalent interactions, including salt-bridges, hydrogen bonds, and π-stacking between aromatic residues and the phenanthroline ligand, are common, and markedly different from those seen in the amyloid-β peptides alone.